Evaluation of vitamin-D status in premenopausal and postmenopausal type-2 diabetic women and its relation to glycemic control - Kotwal, Shivwani D.; Bhat, Anjali N.; Yograj, Sabita; Kotwal, Suresh (International Journal of Research in Medical Sciences, 2020)
Background: Vitamin D deficiency is a public health problem around the world. In 2008, it was estimated that 1 billion persons present with vitamin D insufficiency or deficiency. Vitamin D is obtained through exposure to ultraviolet B (UVB) sunlight as well as nutritional sources. Despite the high UVB sunlight exposure in tropical countries, studies suggest Vitamin D deficiency is highly prevalent. Vitamin D is believed to help improve the body’s sensitivity to insulin, the hormone responsible for regulating blood sugar levels, thus reducing the risk of insulin resistance, which is often a precursor to Type-2 diabetes. Aim and objective of the study was to evaluate and compare the Vitamin-D levels in Premenopausal and Postmenopausal Type-2 Diabetic women and to evaluate if their Vitamin-D levels have any co-relation with their glycemic control. Methods: The study was conducted in Government Medical College Jammu and its associated hospital on 60 Type-2 Diabetic women, 30 premenopausal and 30 postmenopausal. Vitamin-D [25(OH) Vitamin D] levels were assessed by Chemiluminescence method in the Biochemistry Lab. of Govt. Medical College Jammu. Blood sugar levels, both fasting and postprandial, were assessed by Glucose oxidase-peroxidase method in the same Lab. HbA1C was assessed by HPLC [High Performance Liquid Chromatography] assay. Results: Vitamin-D deficiency [Vitamin-D levels <20 ng/ml] was seen in 16.67% of premenopausal type-2 diabetics and in 36.67% postmenopausal type-2 diabetics. This was not related to the glycemic control as HbA1C was increased in both the groups. Conclusions: Vitamin-D deficiency is more prevalent in postmenopausal Type-2 diabetics, as compared to premenopausal type-2 diabetics.